An Investigation of Teaching-Learning Process and Measurement and Evaluation in Elementary English Course Curriculum with the Communicative Language Approach (Teachers’ Views) - Körhasanoğulları, Neşe; Çam Aktaş, Bilge (Anadolu Üniversitesi Eğitim Fakültesi dergisi, 2024)
This study aimed to determine how teachers use the communicative language approach in the learning-teaching process and measurement-evaluation dimensions while implementing the 2018 Primary English Course (Grades 2-8) Curriculum. Embedded single case study design, one of the qualitative designs, was used in this study. The study group included 14 primary education English language teachers instructing different grades in public schools in Eskişehir, Turkey. Data were collected through semi-structured interviews with teachers and analyzed by content analysis. The findings demonstrated that communicative language approach could not be implemented in the classroom due to physical problems in the teaching-learning process, student reluctance and lack of readiness, teachers' initial failure to analyze the learner goals and styles, the lack of the predominant employment of the target language, partial inclusion of the activities determined by the communicative language approach in the course, preference of grammar instruction, partial utilization of group activities, the lack of using authentic materials, immediate correction of learner mistakes, inability to adopt the communicative language roles such as initialization of communication, providing resources and preference of traditional roles, and inability to measure the four basic language skills due to systemic measurement and evaluation errors.